Borax as a lubricant in powder metallurgy (2014)
This paper reported the first results of the investigation of the use of borax (di sodium tetraborate decahydrate) ® Scharlau , as a lubricant powder metallurgy. Two groups of samples were prepared by adding in the first group, the commercial lubricant zinc stearate and in the second group the powder borax in concentrations of 0.5 % by weight, using as matrix powder metallurgy Ancor Steel ® 1000 iron. Ancor Steel 1000 was mixed with lubricants in a rotational homogenizer for 30 minutes; the sampleswere compacted at 700 MPa in a uniaxial press of 15 tons. DSC-TGA analysis of the mixture with borax was realized. The specimens were sintered in a plasma reactor at 1000 for 30 minutes, with a combined atmosphere of hydrogen and argon. Microhardness and density of the sintered samples was haracterized. XRD analysis was realized to detect possible compounds formation by interaction of borax. This paper shows that borax can be used as a lubricant in powder metallurgy.